2019
DOI: 10.1111/fare.12370
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing Sensitivity and the Subjective Experience of Parenting: An Exploratory Study

Abstract: Objective To explore the relationship between sensory processing sensitivity (SPS) and parental subjective experience (PSE). Background SPS is a temperament trait characterized by greater sensitivity to environmental and social stimuli; no previous research has examined the relation of SPS to PSE (e.g., how much parents feel parenting is difficult or feel connected to their child). Method In the first of two online studies, mothers were unaware of the study's relation to SPS (N = 92). In the second, mothers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…These results, compatible with prior research, showed that highly sensitive individuals are prone to more negative emotional states under challenging conditions (e.g., Aron et al, 2005). More specifically, Aron et al (2019) found that mothers high in SPS experienced parenting as more difficult than mothers low in SPS. That may also be the case in the current study, where the vast majority of the participants were mothers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results, compatible with prior research, showed that highly sensitive individuals are prone to more negative emotional states under challenging conditions (e.g., Aron et al, 2005). More specifically, Aron et al (2019) found that mothers high in SPS experienced parenting as more difficult than mothers low in SPS. That may also be the case in the current study, where the vast majority of the participants were mothers.…”
Section: Discussionsupporting
confidence: 90%
“…These behaviors also might be experienced as inconsistent parenting. Aron et al (2019) explored the relationship between SPS and parental subjective experience and found that although mothers high in SPS experienced parenting as more difficult, parents (both fathers and mothers) high in SPS were more in attunement with their child (i.e., child centeredness).…”
Section: Personality and Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…So, physiological self‐regulation and negative emotional reactivity seem to be susceptibility markers during the early sensitive period, but they are not later during development, when it would be other temperamental traits that capture this susceptibility. Whereas in early adolescence, sensory processing sensitivity is a temperament trait that has been widely studied as a marker of susceptibility (Aron et al, 2019), our findings point to low SH as a possible candidate for this at the beginning of middle childhood.…”
Section: Discussionmentioning
confidence: 56%
“…So, physiological self-regulation and negative emotional reactivity seem to be susceptibility markers during the early sensitive period, but they are not later during development, when it would be other temperamental traits that capture this susceptibility. Whereas in early adolescence, sensory processing sensitivity is a temperament trait that has been widely studied as a marker of susceptibility(Aron et al, 2019), our findings point to low SH as a possible candidate for this at the beginning of middle childhood.4.1 | Strengths, limitations, and future studiesOur study contributes to the scarce body of knowledge regarding the effects of fathering on RA in children with different temperament.First, the study focused on the role of fathers in childrearing; most parenting studies do not include fathers nor do they control for fathers' effects on children's outcomes. Moreover, when fathers are included, measures of fathering are often derived from assessments made by mothers.…”
mentioning
confidence: 79%